1987
DOI: 10.1136/emj.4.1.33
|View full text |Cite
|
Sign up to set email alerts
|

'Hunt the thimble': a study of the radiology of ingested foreign bodies.

Abstract: SUMMARYThe role of radiology in the management of patients with a history of ingested foreign bodies is reviewed in a retrospective study over a 2-year period in a Children's Hospital. If radiography was confined to those children who have a clinical history suggestive of foreign body impaction in the oesophagus, a foreign body aspiration or having swallowed a button battery, the work load and unnecessary radiation arising from this practice could be halved. This study demonstrates another misuse of radiologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

1991
1991
2006
2006

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 14 publications
2
1
0
Order By: Relevance
“…Each year, an estimated 25,234 children are treated in emergency departments for coin-related choking episodes, which represents a rate of 43 per 100,000 population. Consistent with what has been observed by other investigators, this study discloses as the most vulnerable children are toddlers [3,[7][8][9]11,[13][14][15]. Emergency rooms treat over 1 per 1000 children between the age of 1 and 3 years after an episode of choking.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Each year, an estimated 25,234 children are treated in emergency departments for coin-related choking episodes, which represents a rate of 43 per 100,000 population. Consistent with what has been observed by other investigators, this study discloses as the most vulnerable children are toddlers [3,[7][8][9]11,[13][14][15]. Emergency rooms treat over 1 per 1000 children between the age of 1 and 3 years after an episode of choking.…”
Section: Discussionsupporting
confidence: 88%
“…Coins do remain the most common foreign body for children [3,[7][8][9][10][11]. Conners et al [12] conducted a survey, which indicated that 4% of all children had a history of swallowing a coin.…”
Section: Discussionmentioning
confidence: 99%
“…One large series has shown that a lack of oesophageal symptoms means that the coin has passed or will pass through the lower oesophageal sphincter. 2 We agree with Messrs Stringer and Capps's recommendation of obtaining a chest and neck radiograph irrespective of symptoms as reports of rare but potentially fatal complications, including oesophageal perforation3 and oesophagoaortic fistula,4 in asymptomatic patients are sufficient indication for routine radiography. A foreign body that appears to be in the oesophagus in a posteroanterior chest x ray film could be in the trachea or proximal bronchial tree, and a lateral view may be necessary to differentiate this.…”
Section: Douglas Modelsupporting
confidence: 80%